URBAN PROJECT “WHAT IS YOUR HISTORY?” (City: History, Culture, Society, 2020)
The report is dedicated to the project "What is your history?", which is been implementing by Zaporizhzhia scientific society named after Yakiv Novytskyi with the support of the U.S. Agency for International Development. The project is focused on promoting the history of three Ukrainian cities (Zaporizhzhia, Berdyansk and Melitopol).
Keywords: urban history; project; Zaporizhzhia; Berdyansk; Melitopol